Ku Band Rotary Joint Design for SNG Vehicles - Torpi, Hamid; Bostan, Salih Mehmed (SPOLECNOST PRO RADIOELEKTRONICKE INZENYRSTVI, 2015)
A wideband I-type rectangular waveguide rotary joint (RJ) is designed, simulated and built. It has an excellent performance over the whole Ku Band (10.7 - 14.5 GHz) where the return loss is less than -23 dB at its highest and the insertion loss is below 0.4 dB. The rotary joint is specifically designed for satellite news gathering (SNG) vehicles providing elevation and azimuthal movement to the antenna and matching polarization when it is needed at the feed. It can also be used in other high power microwave applications, where rotation ability of the antenna is a must during the transmission such as radars.
Keywords: Ku-band; rotary joint; ridge waveguide; SNG vehicle; quarter-wave transformer; RIDGED WAVE-GUIDE; SECTIONS; Engineering